2015
DOI: 10.1007/s11664-015-4109-6
|View full text |Cite
|
Sign up to set email alerts
|

Strength of MWCNT-Reinforced 70Sn-30Bi Solder Alloys

Abstract: In this study, the effect of Cu-coated multi-walled carbon nanotubes (MWCNTs) on the tensile strength of 70Sn-30Bi solder alloy has been investigated. Copper was first deposited onto metal-activated MWCNTs by an electroless process and confirmed with a scanning electron microscope and energy dispersive spectroscopy. Sn-Bi alloy solder was reinforced with Cucoated MWCNTs with additions of 0.5 wt.%, 1 wt.%, 2 wt.%, and 3 wt.%, respectively. 70Sn-30Bi solder was produced by melting pure tin and bismuth in an iner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Additionally, they also demonstrated that the doping of Ag-MWCNTs was effective to suppress the growth of IMC thickness of Sn-58Bi solder joint [35]. Similar phenomenon was also observed in the Sn-58Bi solder with the incorporation of Ni-coated CNTs [103] and Cu-coated CNTs [104]. Ma and Wu [105] reported that the thickness of total IMC layers decreased by 56.31% compared with the plain Sn5-8Bi-0.7Zn solder joint when the doping of GNSs was 0.114 wt%.…”
Section: 22supporting
confidence: 54%
See 1 more Smart Citation
“…Additionally, they also demonstrated that the doping of Ag-MWCNTs was effective to suppress the growth of IMC thickness of Sn-58Bi solder joint [35]. Similar phenomenon was also observed in the Sn-58Bi solder with the incorporation of Ni-coated CNTs [103] and Cu-coated CNTs [104]. Ma and Wu [105] reported that the thickness of total IMC layers decreased by 56.31% compared with the plain Sn5-8Bi-0.7Zn solder joint when the doping of GNSs was 0.114 wt%.…”
Section: 22supporting
confidence: 54%
“…In recent years, with the appearance of CNTs and graphene, some investigations had been carried out to modify the Sn-Bi solders by the addition of CNTs and graphene [35, 36, 38, 61, 103-106, 108, 109]. Billah and Chen [104] researched the influence of Cu-coated MWCNTs on the mechanical properties of 70Sn-30Bi solder. It was found that the tensile strength of composite solder was proportional to the doping of MWCNTs, which increased by 47.6% when the addition of MWCNTs was 3 wt%.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The microstructure characteristics of solder alloys inevitably control their mechanical properties (El-Taher et al , 2021; Hammad and Ragab, 2019). The heterogeneous nucleation points increased with the Sb doping, which resulted in the diminution of grain size and the generation of more grain boundaries to hinder dislocation movement (Sun et al , 2016; Bakshi and Agarwal, 2011; Sharma et al , 2015; Billah and Chen, 2015). The strengthening mechanism conforms to the classical Hall–Petch relation (Armstrong, 2014).…”
Section: Resultsmentioning
confidence: 99%